Inovasi Produk Olahan Asam Jawa Sebagai Komoditas Hutan Bernilai Ekonomi Untuk Pemberdayaan Ekonomi Masyarakat Desa Jembatan Kembar Timur - Ahmad Rifki Fathoni; Dian Muharrani Assurok; Nazwa Dalia Ingeswari; Juan Arqy Maesifa; Amrina Rosyada; Ilham Wahyudin; Rista Oktaneva; Indriyani Rahma; Intan Komalasari Saputri; Nisa Fitriani; Faturrahman Faturrahman (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Community empowerment and development efforts continue to be carried out by the academic community of the University of Mataram. The main objective of this program is to enhance the added value of local commodities and create sustainable home-based business opportunities in Jembatan Kembar Timur Village, West Lombok, with a focus on a “creative economy” based on tamarind processing. The core activities included technical training in the production of tamarind candy and packaged tamarind, packaging design, branding, and marketing strategies. The results of the program showed that 15 participants, consisting of women from the Family Welfare Movement (PKK) and young women, enthusiastically participated in the socialization and training sessions on tamarind candy and packaged tamarind production, and expressed strong interest in further developing tamarind-based products. Upon completion of the training, participants were able to independently produce tamarind candy and packaged tamarind. At the final stage, participants were introduced to attractive packaging as well as virtual marketing techniques through social media. This program is expected to open up new entrepreneurial opportunities for the community of Jembatan Kembar Timur Village